AIDS, a hidden threat to agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Every day, nearly 9,000 people world-wide become infected with HIV, the virus that causes AIDS. The continent of Africahas been the most seriously hit, but the epidemic has spread throughout Asia and is increasingly evident in the Caribbean and...